2016
DOI: 10.1016/j.aquaculture.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing fish meal-free commercial diets for Nile tilapia, Oreochromis niloticus

Abstract: A feeding trial was conducted in a closed recirculating aquaculture system with Nile tilapia Oreochromis niloticus juveniles (mean weight, 6.81 g) to examine the response to a practical diet containing protein primarily from menhaden fish meal (FM) and soybean meal (SBM) (control, Diet 1) or to diets with decreasing ratios of PBM to SBM (Diets 2-7; dose-response) as a total replacement for digestible protein from FM, and the efficacy of 1% supplemental taurine (Tau) at the highest level of plant protein inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
2
22
2
3
Order By: Relevance
“…In the case of tilapia, a wealth of alternative protein sources is available and in use. For some of these ingredients, the apparent nutrient digestibility has been reported already, for example, cottonseed meal and sunflower meal (SFM; Aanyu, Ondhoro, Ganda, Kato, & Basiita, ; El‐Saidy & Gaber, ), feather meal (Guimarães, Pezzato, & Barros, ), dried distillers grains with solubles (DDGS) (Schaeffer, Brown, Rosentrater, & Muthukumarappan, ), rice bran (RB) (Guimarães, Pezzato, Barros, & Tachibana, ), rapeseed (Borgeson, Racz, Wilkie, White, & Drew, ) and soybean meal (SBM) (Koch et al, ; Lin & Luo, ; Vidal et al, ). The substitution of fish meal coincides with an increased variability in dietary nutrient/ingredient composition.…”
Section: Introductionmentioning
confidence: 96%
“…In the case of tilapia, a wealth of alternative protein sources is available and in use. For some of these ingredients, the apparent nutrient digestibility has been reported already, for example, cottonseed meal and sunflower meal (SFM; Aanyu, Ondhoro, Ganda, Kato, & Basiita, ; El‐Saidy & Gaber, ), feather meal (Guimarães, Pezzato, & Barros, ), dried distillers grains with solubles (DDGS) (Schaeffer, Brown, Rosentrater, & Muthukumarappan, ), rice bran (RB) (Guimarães, Pezzato, Barros, & Tachibana, ), rapeseed (Borgeson, Racz, Wilkie, White, & Drew, ) and soybean meal (SBM) (Koch et al, ; Lin & Luo, ; Vidal et al, ). The substitution of fish meal coincides with an increased variability in dietary nutrient/ingredient composition.…”
Section: Introductionmentioning
confidence: 96%
“…However, more investigations are required to evaluate the performance of different combinations of alternative constituents to prepare a balanced tilapia diets. Koch et al (2016) demonstrated that the available economical feeds for O. niloticus entail nutrient reduction or are unbalanced, such that the decreased feed utilization is likely to release unutilized protein, carbohydrates, and other constituents into, and cause eutrophication of, adjoining water reserviors (Montanhini Neto and Ostrensky, 2015). Meanwhile, Webster et al (1999) reported that compounding animal and plant protein sources with additional amino acid profiles may enhance the possibility of nutrient inadequacy that could adversely affect fish growth.…”
Section: Introductionmentioning
confidence: 99%
“…Future evaluations of CSM as alternative protein source to FM in tilapia nutrition should take into account that adding FM to tilapia feed formulations is rather low -ordinarily circa 2 -5 % (Chiu et al, 2013). As a matter of fact, the use of FM in tilapia diets is possibly unnecessary (Koch et al, 2016). Consequently, it is logical to use CSM as replacement to SBM as protein source, or as it is a good source of digestible lysine, CSM could replace costly synthetic lysine sources.…”
Section: Estimation Of Price Range For the Use Csm As Dietary Proteinmentioning
confidence: 99%